2019
DOI: 10.21053/ceo.2018.00717
|View full text |Cite
|
Sign up to set email alerts
|

Nasality Changes With Age in Normal Korean-Speaking Adults

Abstract: ObjectivesThis study was performed to investigate the effects of aging on nasality and the influence of age-related changes in nasal cavity volume and nasal patency on nasality.MethodsA total of 180 healthy Korean-speaking adult volunteers, who had no nasal or voice-related complaints, were enrolled in this study. Nasometry, acoustic rhinometry, and rhinomanometry were performed to obtain the nasalance score, nasal cavity volume, and nasal resistance, respectively. Changes in these parameters with age were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…This could also represent another key-point in the explanation of the different prevalence of COVID infection by gender. Nevertheless, a progressive and relatively linear increase in nasal cavity volume with increasing age coupled with an age-dependent decrease of nasal resistance might represent determinants for a higher prevalence of COVID in the elderly population [29].…”
Section: Sars-cov-2 Pathogenesis: Implications For Older Adultsmentioning
confidence: 99%
“…This could also represent another key-point in the explanation of the different prevalence of COVID infection by gender. Nevertheless, a progressive and relatively linear increase in nasal cavity volume with increasing age coupled with an age-dependent decrease of nasal resistance might represent determinants for a higher prevalence of COVID in the elderly population [29].…”
Section: Sars-cov-2 Pathogenesis: Implications For Older Adultsmentioning
confidence: 99%
“…Several recent studies identified advanced age as a common potential risk factor associated with the course of the coronavirus disease 2019 (COVID-19) ( 6 – 9 ). More recently, changes of anatomical respiratory structure with aging ( 10 ), immunosenescene ( 11 ), and inflammaging ( 12 ) may represent three major determinants for a higher prevalence and mortality of COVID-19 infection in elderly populations. Further, age-related alterations in metabolism underlay changes in innate and adaptive immunity ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Advanced age has also been identified as an independent risk factor of COVID-19 5 , 15 , 16 . The underlying mechanisms could include changes of anatomical respiratory structure with aging 17 , immunosenescene 18 , and inflammaging 19 , which would, respectively, facilitate entry of SARS-CoV-2, weaken anti-viral immunity, and promote a cytokine storm, leading to multiple organ damages. Further, age-related alterations in metabolism are known to underlay changes in innate and adaptive immunity 20 , which also contribute to the weakening of immunity.…”
Section: Discussionmentioning
confidence: 99%